Dynamics of spreading of SARS‐CoV‐2 in a Belgian hemodialysis facility: The importance of the analysis of viral strains. Issue 4 (30th November 2021) - Labriola, Laura; Ruelle, Jean; Scohy, Anaïs; Seghers, François; Perlot, Quentin; De Greef, Julien; Desmet, Christine; Romain, Cécile; Yombi, Jean Cyr; Rodriguez‐Villalobos, Hector; Kabamba, Benoît; Jadoul, Michel
Abstract: In‐center maintenance hemodialysis (HD) patients are at high risk of acquiring coronavirus disease 2019 (COVID‐19) by cross‐contamination inside the unit. The aim of this study was to assess retrospectively the dynamics of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) transmission during the very first pandemic phase (March–July 2020) in a cohort of in‐center maintenance HD patients and in nurses the same HD facility, using a phylogenetic approach. All SARS‐CoV‐2 quantitative reverse‐transcription polymerase chain reaction positive patients and nurses from our HD unit‐respectively 10 out of 98, and 8 out of 58‐ and two other positive patients dialyzed in our self‐care unit were included. Whole‐genome viral sequencing and phylogenetic analysis supported the cluster investigation. Five positive patients were usually dialyzed in the same room and same shift before their COVID‐19 diagnosis was made. Viral sequencing performed on 4/5 patients' swabs showed no phylogenetic link between their viruses. The fifth patient (whose virus could not be sequenced) was dialyzed at the end of the dialysis room and was treated by a different nurse than the one in charge of the other patients. Three nurses shared the same virus detected in both self‐care patients (one of them had been transferred to our in‐center facility). The epidemiologically strongly suspected intra‐unit cluster could be ruled out by viral genome sequencing. The infection control policy did not allow inter‐patient contamination within the HD facility, in contrast to evidence of moderate dissemination within the nursing staff and in the satellite unit. Epidemiologic data without phylogenetic confirmation might mislead the interpretation of the dynamics of viral spreading within congregate settings. Highlights: In‐center maintenance hemodialysis (HD) patients are at high risk of acquiring coronavirus disease 2019 by cross‐contamination inside the unit. In this study we assessed the dynamics of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) transmission in a cohort of in‐center maintenance hemodialysis patients and in nurses the same HD facility in Brussels, Belgium, using whole‐genome viral sequencing and phylogenetic analysis. All SARS‐CoV‐2 quantitative reverse‐transcription polymerase chain reaction (RT‐qPCR) positive patients (10 out 98) and nurses from our HD unit (8 out 58) and two other positive patients dialyzed in our self‐care unit were included. An intra‐unit cluster was suspected because five SARS‐CoV‐2 RT‐qPCR positive patients were dialyzed in the same room at the same time three times weekly. The epidemiologically strongly suspected intra‐unit cluster could be ruled out by viral genome sequencing. In contrast, three nurses shared the same virus detected in both self‐care patients (one of them had been transferred to our in‐center facility). Epidemiologic data without phylogenetic confirmation might mislead the interpretation of the dynamics of viral spreading within congregate settings.